Introduction to electron microscopy for biologists - Allen, Terence D. (Methods in cell biology, 2008)
This volume demonstrates how cellular and associated electron microscopy contributes to knowledge about biological structural information, primarily at the nanometer level. It presents how EM approaches complement both conventional structural biology (at the high end, angstrom level of resolution) and digital light microscopy (at the low end, 100-200 nanometers).--Provided by publisher.